PENERAPAN JUST IN TIME DALAM PERSEDIAAN BAHAN BAKU PEMBUATAN KERIPIK SINGKONG - Jumadi Suratman; Rini Halila Nasution; Yetti Meuthia Hasibuan; Ardilla Ardilla; Jaka Tri Hadiyatna (Universitas Harapan Medan, 2020)
The New Sustenance Trading Business is a business engaged in snacks, precisely making cassava chips. In this business, there is a residue and insufficient use of supplies of supporting raw materials such as cooking oil, garlic, and table salt. Therefore, it is necessary to control inventory with a method, namely Just In Time (JIT). Based on the results of the research by applying Just In Time (JIT) to get the total cost of cooking oil inventory of Rp. 1,174,888, garlic Rp. 272,673, table salt Rp. 516,218 and when applying the Just In Time (JIT) method there was a saving in the cost of cooking oil inventory of Rp. 1,206,705, garlic Rp. 1,550,542 and table salt Rp. 668,048.